Karakterisasi Sucrose-Free Hard Candy Dengan Suplementasi Ekstrak Cabe Jamu (Piper retrofractum Vahl) - Mojiono, Mojiono; Supriyanto, Supriyanto; Kurniawati, Andriani Agusbudi (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
Hard candy is a popular confectionery product typically made from a mixture of sweeteners (commonly sucrose) and fruit extracts or food additives to modify flavour, colour, and texture. This study aimed to develop sucrose-free hard candy formulations using glucose and fructose blends supplemented with Javanese long pepper (Piper retrofractum Vahl) extracts. The evaluated characteristics included colour (RGB notation), pH, solubility time, antioxidant activity, and hedonic profile. The experiment followed a non-factorial Completely Randomised Design (CRD) consisting of different sweetener ratios (in gram): FR0 (sucrose:glucose, 60:50), FR1 (fructose:glucose, 40:70), FR2 (fructose:glucose, 35:75), and FR3 (fructose:glucose, 30:80), carried out at triplicates. Results showed that FR0 had a significantly higher RGB colour value (73.63) than FR1–FR3 (29.26–36.60). Visually, FR0 appeared brighter with a yellowish-brown in colour, whereas other samples exhibited a darker red dominance. The pH of candies ranged from 3.17 to 3.99, while solubility time varied between 18.00 and 21.46 min. Antioxidant activity remained low (<5%) while sensory evaluation revealed FR3 (30 g fructose:80 g glucose) as the most preferred formulation for aroma based on a hedonic test by untrained panellists. These findings carry significant industrial implications, suggesting that formulation FR3 can be selected for developing sucrose-free hard candy products, with colour modification to enhance visual appeal. Furthermore, this study is expected to contribute to the development of functional confectionery products utilising local ingredients and reformulation of products using alternative sweeteners.